Assessment of Knowledge and Attitude of Breast and Ovarian Cancer Patients Regarding Hereditary Breast-Ovarian Cancer Syndrome at a Tertiary Cancer Institute: A Cross-Sectional Observational Study - Pramanik, Raja; Vats, Shubhra; Mitra, Sanchita; Deo, SVS; Kumar, Lalit; Gogia, Ajay; Khurana, Sachin; Batra, Atul (Indian Journal of Medical and Paediatric Oncology, 2023)
Introduction Hereditary breast and ovarian cancer (HBOC) syndrome affects a significant proportion of our breast and ovarian cancer patients. Mutations in genes, for example, BRCA1 and 2, confer a high risk of acquiring certain malignancies, including breast cancer in both men and women, and ovarian cancer in women. Mutation carriers provide a unique opportunity for healthcare professionals to intensively screen and detect malignancy at an early and curable stage. But, patient awareness and acceptance are the keys to the success of these strategies.Objective There is a need to assess the awareness of the patients in this field as the patients come from varied backgrounds, and differ in their socioeconomic profiles, educational backdrop, and cultures. In this study, done prior to establishing our cancer genetics clinic, we evaluated the knowledge and attitude toward HBOC in patients with breast cancer and ovarian cancer.Materials and Methods This cross-sectional observational study was conducted on patients registered in IRCH-AIIMS, who has a diagnosis of breast cancer or ovarian cancer using a self-administered questionnaire based on knowledge and attitude. The sample population included 84 women aged between 25 and 80 years. A binary response was given to knowledge questions, whereas a categorical response was given to attitude questions. The overall data was computed using STATA v13 software.Results According to the findings of the study, 39.3% (5.11/13) of the patients were aware of hereditary cancer. Knowledge among the targeted population was poor, but 72.1% (37.5/52) of the population had a neutral attitude toward learning more about hereditary cancer tests. Only 23/84 (27%) people had heard of genetic counseling. Seventy of eighty-four (83%) patients agreed that they would opt for a genetic test if indicated. While 60/84 (72%) of the population wanted to interact with a counselor over a telephonic call, only 41/84 (49%) wanted to interact in person.Conclusion We concluded from the study that breast and ovarian cancer patients in our clinic have little understanding of HBOC syndrome but have a neutral attitude toward learning more about it.
Keywords: hereditary breast and ovarian cancer; mutation; genetic counseling